Effect of tolerogenic peptide administration on pathogenic antigen-experienced T cells - McPherson, Rhoanne Catherine (The University of Edinburgh, 2012)
The administration of soluble antigenic peptides is known to be effective at inducing tolerance in naïve antigen-reactive CD4+ T cells. This observation forms the basis of antigen-based therapy, which offers the potential to specifically target the auto-reactive CD4+ T cells involved in driving autoimmune disease pathogenesis, whilst leaving the rest of the immune system intact. The prophylactic administration of soluble autoantigen-derived peptides has proven to be effective at inhibiting disease induction in various experimental models of autoimmune disease. However, the clinical requirement is to switch off the activated antigen-experienced CD4+ T cells that are present during an ongoing immune response. The effect of soluble peptide administration of antigenexperienced CD4+ T cells is poorly understood, and several clinical trials using peptides in multiple sclerosis patients had to be halted due to the exacerbation of disease. This thesis characterises the effect of soluble peptide administration on pathogenic antigen-experienced CD4+ T cells, using experimental autoimmune encephalomyelitis (EAE) as a model of autoimmune disease of the central nervous system. Using traceable myelin-reactive T cells from Tg4 mice, it was determined that soluble peptide administration induces substantial expansion of antigen-experienced CD4+ T cells. Despite the increase in number, these cells were no longer able to induce EAE. Production of effector cytokine was significantly decreased in peptide treated antigen-reactive CD4+ T cells, and this correlated with high level expression of the co-inhibitory molecule PD-1. The induction of tolerance in both naïve and antigen-experienced CD4+ T cells was found to be dependent upon PD-1 expression, whereby peptide treatment of naïve and antigen-experienced CD4+ T cells that were deficient in PD-1, did not inhibit disease induction. This thesis identifies a novel mechanism of peptide-induced tolerance in CD4+ T cells, and demonstrates that soluble peptide administration can induce tolerance in antigen-experienced T cells.
Keywords: T cells; peptide tolerance; PD-1